TEACHING ACTION VERBS TO YOUNG LEARNERS - Olimova Nodira Oybekovna (Scholar Express Journal, 2021)
All verbs express different occurrences, states, and actions done by a subject in a sentence. Action verbs are the most known verbs which make them the perfect start for all English learners from native speakers to ESL students. Also, teaching action verbs is very helpful for children when they start learn English language. With the help of certain kinds of methods it can be really easy and reasonable. In this case, children these verbs without even thinking about it, it is something that comes naturally to their mind.
Keywords: Action; TPR; verb; game; movement; children